Gender Issues in the Horrors of Ira Levin - Šrédlová, Karolína (Univerzita Pardubice, 2021)
The thesis depicts the gender inequality in three selected horrors of Ira Levin. The nature and history of the horror genre is outlined. The thesis also deals with concepts such as gender or feminism. Based on gender stereotypes, characters from selected novels are analyzed. The behaviour and reactions of the characters helped the author determine Levin's perception of female oppression. In Conclusion, the acquired insight is summarized, from which the author deduced the role of women in Levin's works.
Otázky genderu v hororech Iry Levina
Keywords: horor; gender; feminismus; patriarchát; Levin, Ira; stereotypy; horror; gender; feminism; patriarchy; Levin, Ira; stereotypes